Pengaruh Pendidikan Kesehatan tentang DHF Menggunakan Metode Audiovisual terhadap Tingkat Pengetahuan Anak - Warsini, Warsini; Sriwiyati, Lilik (Jurnal Kesehatan Holistic, 2020)
Dengue Hemorrhagic Fever (DHF) has become a health problem in Indonesia for the past 47 years. An increase in DHF cases has occurred since 1968 and was still happened until 2015. One alternative to decrease the incidence rate of DHF was increase knowledge using health education. The aim of the study was to know the effect of health education about DHF using audiovisual methods on the level of knowledge in children. This research was observational analytic that was quasi experiment with pre and post experimental design. Subjects were 46 students in Gentan 01 Elementary School, sampel has been taken using saturated sampling techniques. The Results showed that the value of respondents' knowledge after giving health education using audiovisual media (Mean= 82.39; SD= 7.58) is greater than before giving health education (Mean= 76.09; SD= 9.00) with Effect Size (Cohens'd ) = 1.1753 and p = 0,001. The conclusion of this research showed there is an effect of health education about DHF using audivisual methods on the level of knowledge of children (p = <0.001; 95% CI -8.391 to -4.218).